Picture yourself learning microsoft office 2007 - Koers, Diane ([S.l.] : Cengage Learning PTR, 2007)
Featured in the four-color, visual Picture Yourself series, Picture Yourself Learning Microsoft Office 2007 is a valuable resource for all readers, beginner to intermediate. Clear, step-by-step instructions walk you through the basics of each application from beginning to end. Helpful tips provide additional information and advice to enhance your Office 2003 experience and help meet your needs. Picture Yourself Learning Microsoft Office 2007 is packed with information useful to those who have purchased their first computer and are learning Office 2007 for the first time. Those who have experience with older versions of Office will find this book an excellent way to help them get up to speed on their computing experience, by way of the over 1,000 screenshots to guide your way. You have the option of reading the book from cover to cover, or simply reading the individual programs you are interested in.
Keywords: Business--Computer programs -- Electronic spreadsheets--Computer programs